A Study in Buildability Aspect Caused by Different Shape and Geometry of a Nozzle in Printing of Abrasive Materials - Abu Bakar, Muhammad Syamir; Sa’ude, Nasuha; Hj Ibrahim, Mustaffa; Natasha Ismail, Nur Amira (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The 3D printing technologies is an eco-friendly variant and much easier, giving wider build customizability when compared to the traditional method, this paper focused on the buildability aspect that affected by the nozzles. The main objectives are to find the best nozzle size and geometry to print clay and a good buildability. Six types of nozzles will be used, three of them are in circular shape while the others are in rectangular shape and having different diameter. The study is using a clay admixture that are kept constants for all the testing and experiment, which are 600 gram of clay and 60 millilitres of water. From the observed data, rectangular shape nozzle gave the outcome and results. 3 mm nozzle with rectangular shape can 3D print clay up to 8 layers without collapse or bend on the contour. However, buildability can be affected on other aspects, such as printing speed, parameter setting, extrusion speed and the mixing design. For future work, aspect like mention earlier can be explored to achieve a good buildability.